ANTIBACTERIAL ACTIVITY OF MODERATELY VOLATILE COMPONENTS OF THE OIL EXTRACTED FROM THE SEEDS OF DACRYODES EDULIS G. LAM - C MORDI, RAPHAEL; OLASEHINDE, GRACE I; P OKEDERE, ADEBOLA; N ELEGWULE, ARNOLD; AYO-AJAYI, JOAN I; O JOHNATHAN, HASSANA; E ONIBOKUN, ADEOLA; A AJAYI, ADESOLA; O UCHENNA, DANIEL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Dacryodes edulis is a versatile plant in many African countries, as its various parts are employed to treat several diseases. Like most plants used in traditional medicine, the possible mechanism by which D. edulis functions is still unknown. This study was designed to investigate the components of the plant seed with a view of justifying its use as traditional medicine. Methods: The seed oil of D. edulis was exhaustively extracted with a Soxhlet extractor from 500 g seeds and 200 g seeds of D. edulis using ethanol and petroleum ether as solvent, respectively. The extraction solvent was removed to obtain the oil which was then subjected to antimicrobial activity test to determine its activity against the following clinical isolates namely Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus cereus, and Escherichia coli using gentamycin as positive control. Phytochemical screening and gas chromatography-mass spectrometry (GC-MS) analyses were carried out following standard methods Results: Ethanolic extract resulted in a higher percentage of oil yield (11.6%) than petroleum ether (5.3%). D. edulis seed oil showed remarkable activity against Gram-negative and Gram-positive isolates: E. coli, Bacillus spp, and S. aureus but not against P. aeruginosa. The presence of saponins, quinones, cardiac glycosides, terpenoids, and phenol was confirmed during qualitative phytochemical screening, and the preliminary results from GC-MS analysis show the presence of terpinen-4-ol, 4,6,6-trimethyl bicyclo[3.1.1]hept-3-en-2-one, ethyl 14-methyl-hexadecanoate, methyl 19-methyl-eicosanoate, squalene, C-14 to C-18 fatty acids, and their esters. Conclusion: The study, therefore, confirms that the use of D. edulis as component of traditional medicine may be justified.